Monoclinic-tetragonal-monoclinic phase transitions in Eu0.1Bi0.9VO4 under pressure. (2nd September 2019) - Errandonea, D; Garg, A B; Pellicer-Porres, J; Martinez-Garcia, D; Popescu, C
Abstract: The promising technological material Eu0.1 Bi0.9 VO4, has been studied for the first time at room-temperature under high-pressure, up to 24.9 GPa, by means of in situ angle dispersive powder x-ray diffraction (XRD). The compound undergoes two phase transitions at 1.9 and 16.1 GPa. The first transition is from the monoclinic fergusonite-type structure (space group I2/a) to a tetragonal scheelite-type structure (space group I41 /a), being a ferroelastic-paraelastic transformation similar to that previously reported for isomorphic pristine BiVO4 . The second phase transition is first-order in nature. The scheelite-type and the second high-pressure phase coexist in a wide pressure range. A monoclinic structure (space group P21 /n) is proposed for the second high-pressure phase. Both transitions are reversible upon decompression. Details of the different crystal structures are reported. All the three observed structures are composed of network of VO4 tetrahedra and BiO8 (or EuO8 due to the substitution of Bi by Eu) dodecahedra. The room-temperature P–V equation of state and axial anisotropic compressibilities of the fergusonite and scheelite polymorphs are also given. In particular, the isothermal compressibility tensor for the monoclinic fergusonite phase has been calculated.